Wildfire hazards, risks, and disasters - Paton, Douglas (Amsterdam : Elsevier, 2015)
More than 90% of wildfires are caused by human activity, but other causes include lighting, drought, wind and changing weather conditions, underground coal fires, and even volcanic activity. Wildfire Hazards, Risks, and Disasters, one of nine volumes in the Elsevier Hazards and Disasters series, provides a close and detailed examination of wildfires and measures for more thorough and accurate monitoring, prediction, preparedness, and prevention.
10.3 FIRE HISTORY AND CURRENT STATISTICS11.3 FIRE EARLY WARNING SYSTEMS; 12.3 THE CASE OF MEGAFIRES; Index.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on October 30, 2014).
Keywords: Wildfire risk; GARDENING -- Fruit; TECHNOLOGY & ENGINEERING -- Agriculture -- General; Wildfire risk; Electronic books; Electronic books